Morphology of the Eggs of Ornithocoris pallidus (Hemiptera, Cimicidae, Haematosiphoninae). Issue 1 (26th August 2020) - Bastos, Amanda Q; Freitas, Simone P C; Lopes, Catarina M; Gonçalves, Teresa C M; Santos-Mallet, Jacenir R
Abstract: Morphology of cimicid eggs are scarce, and this is the first record for the genus Ornithocoris Pinto, 1927 (Hemiptera: Cimicidae), using scanning electron microscopy (SEM). This genus comprises two species: Ornithocoris toledoi Pinto, 1927 (Hemiptera: Cimicidae) and Ornithocoris pallidus (Usinger, 1959). The eggs of O. pallidus are ellipsoid, and an evident 'lateral flattening', which may give clear asymmetry from the longitudinal axis. The exochorion of the body of the egg and operculum of O. pallidus present spherical or polygonal structures in relief, and pseudomicropyles on the border of the operculum, both differing from Cimex lectularius . The internal face of the operculum is smooth and the border also presented three layers. It was not possible to observe micropyles in the egg of O. pallidus. Bed bugs have a great psychological impact on people, and some people can develop a more or less severe allergic reaction against the bite. Successful control of bed bugs needs serious organization. Studies on egg morphology will add more information to assist in taxonomy studies of O. pallidus and can serve as a basis for control studies because eggs are resistant to insecticides.